Knowledge and practices towards malaria amongst residents of Bushbuckridge, Mpumalanga, South Africa - Khumbulani W. Hlongwana; Alpheus Zitha; Aaron M. Mabuza; Rajendra Maharaj (AOSIS, 2011)
Background: Malaria remains one of the greatest public health challenges worldwide and it is amongst the top killers in sub-Saharan Africa. There is however, a general scepticism about the accuracy of Health Management Information Systems (HMIS) in recording all the episodes of malaria in Africa. Given the importance of community knowledge of malaria, its signs and symptoms, as well as prompt treatment-seeking behaviour, the study assessing adult residents' knowledge and practices in Bushbuckridge provided much needed insights into the Malaria Control Programme (MCP). Objectives: The objectives of this study were to determine the adult residents' knowledge and practices towards malaria in Bushbuckridge, Mpumalanga Province, South Africa. Method: The study was undertaken as a descriptive cross-sectional survey in Bushbuckridge in August 2008. Six hundred and two (602) household heads or their proxies from the randomly selected households in 20 localities were interviewed (one household member per household), using a structured field-piloted questionnaire. Results: Approximately 93% of the respondents had heard about malaria, 84.6% of whom correctly associated it with mosquito bites. The health facility (29.1%) and radio (19.8%) were the main sources of malaria information. Knowledge of signs and symptoms was low, whilst treatment-seeking intention at the health facility was high (99%) with 82% of which would be carried out promptly. Survey data showed an indoor residual spraying (IRS) coverage of approximately 70% and a good understanding of the reasons for spraying. Walls were replastered infrequently and no evidence was established linking it to the removal of insecticide marks on the wall. Conclusion: The study revealed not only that householders possessed an adequate knowledge of malaria, but also that they had positive malaria treatment-seeking intentions. Their knowledge of malaria signs and symptoms was inadequate and required attention. Whilst IRS coverage needed some improvements, the reasons for IRS were well known.